Herb-Fortified Arabica Cascara Infusion as a Functional Beverage - Syabila, Feby Ariani; Supriyanti, Florentina Maria Titin; Zackiyah, Zackiyah (Jurnal Natural Scientiae, 2024)
Cascara is a product derived from the drying of Arabica coffee pulp. It has potential as a functional beverage with health benefits. This study aims to produce a functional beverage from cascara and analyze its organoleptic properties, phytochemical content, antioxidant activity, total polyphenols, and caffeine content of cascara infusion fortified with medicinal plants. The methods utilized in this study included drying, grinding, and sieving, as well as the formulation of cascara with lemongrass (Cymbopogon citratus) and kaffir lime peel (Citrus hystrix) fortificants. The formulations included V1 (C : S = 75% : 25%); V2 (C : J = 75% : 25%); V3 (C : S : J = 50% : 25% : 25%); and V4  (C : S : J = 75% : 12,5% : 12,5%). The analysis included organoleptic evaluation, cascara brewing temperature and time optimization, gravimetric method moisture content evaluation, pH measurement, phytochemical content evaluation, DPPH method antioxidant activity assay, Folin-Ciocalteu method total polyphenol content measurement, and UV-Vis spectrophotometry caffeine content evaluation. The hedonic test results indicated that the most preferred sample was V1, with a score of 3.90 out of 5.00. Moisture content analysis showed that cascara contains 13.36 ± 0.0007% moisture, lemongrass stalks 11.10 ± 0.0043%, and kaffir lime peel 7.63 ± 0.0004%. The pH of all variants had met the standard with a range of 4.18 ± 0.05 - 4.24 ± 0.08. The phytochemical analysis indicated that the control variable of cascara infusion (C) and V2 contained alkaloids, phenolics, and tannins. Meanwhile, V1 contained alkaloids, phenolics, tannins, and terpenoids. All cascara infusion variants contains antioxidant activity ranged between 78,25 ± 0,25 - 79,50 ± 0,63%; total polyphenol 494,25 – 1.500 mg GAE/100g; and caffeine content 392,53 – 409,53 mg/100g. In conclusion, the study found that cascara infusion V1 was the most preferred by taste testers, and all the infusions were rich in antioxidants and other beneficial compounds.